(3QSGdI aj MceI GdCejI aj cdeI COejIs
(3ChdgG (B:s
(3aUd MceI GdCejI ai cdeI COejI COejI CYde Cf GdCSeGA GdBdgjI GdMSfi JWdH HPhGJgG hLhO GdYGde s
(3BNQgG (B:s
(3deG cGf GdNha eY GdVdGd bGd eG Vd UGMHce heG Zhi Ci eG NGa ai NjQJg hHjGf ai EKHGJ GdMjQI hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI eMeO CMeO GdeMGei (B_ (3GdHUQI (B(219 (3N(B) s
Keywords: (3GdeLGejYs